Single-walled carbon nanotubes filled with M OH (M = K, Cs) and then washed and refilled with clusters and molecules. - Thamavaranukup, N; Hoppe, H; Ruiz-Gonzalez, L; Costa, P; Sloan, J; Kirkland, A; Green, M (2004)
Heating single-walled carbon nanotubes (SWNTs) with molten hydroxides MOH (M = K, Cs) gave MOH@SWNT in good yield; high resolution transmission electron microscopy (HRTEM) indicated that CsOH in CsOH@SWNT often adopts twisted 1D crystal structures inside SWNTs; treating MOH@SWNT with water at room temperature removes the soluble hydroxide filling and the resulting SWNTs may then be filled using aqueous solutions of uranyl acetate or uranyl nitrate at rt giving SWNTs filled with UO(2) clusters and uranyl acetate molecules.